(untitled) (Proceedings of Voronezh State University. Series: Geology, 2018)
Information on the deglaciation of the Karelian-Kola region in the late Pleistocene-Holocene and the distribution of building material deposits in the cover of Quaternary sediments has been systematized. It is shown that areal deglaciation dominated in both regions and deposits of sands and sand and gravel mixtures are confined to the areas of dissecting deglaciation in the Kola region and to areal deglaciation in Karelia. In the Kola region, 154 deposits of sand and sand-gravel mixtures and 25 deposits of easily fusible clay were discovered. In Karelia, 369 deposits of sand and sand-gravel mixtures and 71 deposits of easily fusible clay have been explored. Deposits of clays were formed everywhere, mainly under dissecting deglaciation.